The proliferation security initiative as a new paradigm for peace and security - Shulman, Mark R. (Strategic Studies Inst., U.S. Army War College, 2006)
The author examines the Proliferation Security Initiative--a multinational activity launched in 2003 to enable the United States and like-minded countries to interdict the flow of weapons of mass destruction (WMD). This Initiative also may bring dramatic changes the international security system by enabling concerned states to interdict international trade in WMD regardless of the location or nationality of their owners. As such, the Proliferation Security Initiative not only addresses one of the most urgent threats to peace and security that the world has ever witnessed, but it does so in an innovative way that has the potential to change the basic paradigm of peace and security by legitimizing the proportional and discriminating use of force to prevent a great harm. The author argues that the Initiative can be most successful by building broad support through increased transparency and a greater willingness to address forth-rightly the legal challenges that it faces.